2017
DOI: 10.1101/237230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Division of labor during biofilm matrix production

Abstract: Organisms as simple as bacteria can engage in complex collective actions, such as group motility and 28 fruiting body formation. Some of these actions involve a division of labor, where phenotypically 29 specialized clonal subpopulations, or genetically distinct lineages cooperate with each other by 30 performing complementary tasks. Here, we combine experimental and computational approaches to 31 investigate any benefits arising from division of labor during biofilm matrix production. We show that 32 both phe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(112 citation statements)
references
References 58 publications
3
109
0
Order By: Relevance
“…We see this in the bottom-right regions of plots in Figure 5. Wakano et al, 2009;Wilson et al, 2003), and multiple factors can couple together to influence the evolution of cooperation (Dobay, Bagheri, Messina, Kümmerli, & Rankin, 2014) and division of labour (Dragoš et al, 2018) in unexpected ways.…”
Section: Extinctionmentioning
confidence: 99%
See 1 more Smart Citation
“…We see this in the bottom-right regions of plots in Figure 5. Wakano et al, 2009;Wilson et al, 2003), and multiple factors can couple together to influence the evolution of cooperation (Dobay, Bagheri, Messina, Kümmerli, & Rankin, 2014) and division of labour (Dragoš et al, 2018) in unexpected ways.…”
Section: Extinctionmentioning
confidence: 99%
“…Since cells must be within a certain distance to exchange such services, spatial aggregation is considered a prerequisite for multicellular specialization. Spatial effects matter (Durrett & Levin, ; Fletcher & Doebeli, ; McNally et al, ; Wakano et al, ; Wilson et al, ), and multiple factors can couple together to influence the evolution of cooperation (Dobay, Bagheri, Messina, Kümmerli, & Rankin, ) and division of labour (Dragoš et al, ) in unexpected ways.…”
Section: Introductionmentioning
confidence: 99%
“…3). Previous studies demonstrated that secreted biofilm matrix components complement pellicle biofilm formation [20,27] 9 as well as plant colonization [10,11]. Notably, mixing eps and tasA mutant B. subtilis strains results in genetic division of labor, thus increased population productivity both during pellicle biofilm formation at the air-liquid interface and during plant root colonization [11,28].…”
Section: Secreted Biofilm Matrix Components Are Shared Among Mutantsmentioning
confidence: 99%
“…In addition, Spo0A has been later shown to impact protease secretion, toxin production, and biofilm development, thus involved in regulation of genes related to cell fate decision of the bacterium [7]. Formation of biofilm in B. subtilis requires a complex matrix composed of exopolysaccharide (EPS), TasA amyloid fiber, and a surface localized hydrophobin, BslA [8][9][10][11][12][13]. The former two matrix components are essential for the establishment of a floating biofilm on the air-medium interface (referred to as pellicle), the creation of complex vein-like structures on agar medium, or attachment to the root 3 surface of plants [8][9][10]14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation